Inquéritos sorológicos em equídeos e aves silvestres para detecção de anticorpos anti-arbovírus de importância em saúde pública no Brasil - ARAUJO, Francisco Anilton Alves (2011)
This study determined the prevalence of hemagglutination-inhibition antibodies against alphaviruses in horses during an epizootic event by Eastern Equine Encephalitis virus in the state of Paraiba, Brazil, in 2009 and compared the results between the techniques of hemagglutination inhibition and serum neutralization test in microplates. The results of15 arboviruses obtained from serological surveys on horses in Brazil from 2007 to , as well as the results for the arboviruses found in two serological surveys on wild birds in the state of Para, between 2007 and 2008 2009 were analyzed,. In Paraiba, blood was collected from 188 horses during other surveys of 4.402 animals and 544 wild birds. The material was tested by the hemagglutination inhibition technique, neutralization was performed in microplates aiming at virus isolation. In Paraíba, we obtained a true prevalence of 62.2% for Eastern Equine Encephalitis and hemagglutination inhibition test had 79.5% sensitivity and 87.3% specificity . In Brazil, the prevalence rate was 33.3% for arboviruses, 20.6% for flaviviruses, 14.1% for alphavirus and 10.1% for bunyavirus. In birds, the positivity was 28.4%, being 14.7% for alphaviruses, 9.5% for flaviviruses and 7.4% for bunyavirus. There was a high circulation of antibodies against Eastern Equine Encephalitis in inapparent-host animals and the hemagglutination inhibition test can be recommended as screening method. The other arboviruses surveyed were found in animals of the nine states with a significant difference in the prevalence from the motivation of the survey. Migratory birds have proved to be important amplifiers of these agents .